Platelet–leukocyte interaction and platelet activation in migraine: a link to ischemic stroke?. Issue 7 (16th June 2004) - Zeller, J A; Frahm, K; Baron, R; Stingele, R; Deuschl, G
Abstract : Objectives: Migraine has been identified as an independent risk factor for ischemic stroke. Both neurogenic inflammation and platelet activation have been linked to the pathophysiology of migraine. Increased platelet activation results in up-regulation of specific binding to leukocytes which promotes pro-inflammatory leukocyte secretion and their tethering to endothelium, a mechanism that has been demonstrated in stroke and which could provide a link to migraine. We aimed to determine whether platelet–leukocyte aggregation is increased in migraine patients outside an acute attack. Methods: Seventy two patients with migraine according to IHS criteria were compared to a control group (n = 72). Whole blood flow cytometry was used to quantify the activation dependent P selectin on the platelet, and to assess the fraction of platelets bound to the different leukocyte subsets. Results: Migraine patients showed significantly more platelet–leukocyte aggregates compared to the control subjects (p = 0.003). This effect was driven by an increased polymorphonuclear cell–platelet aggregation (p = 0.003) whereas platelet aggregation with monocytes and lymphocytes was not. Platelet activation was also increased (p = 0.001). Conclusions: In migraine pro-inflammatory platelet adhesion to leukocytes occurs during the headache free interval similar to that seen in acute coronary and cerebrovascular syndromes. This may suggest a link between migraine and stroke on a cellular level.